Distribution and antibiotic susceptibility of pathogens isolated from adults with hospital-acquired and ventilator-associated pneumonia in intensive care unit - Zorana M. Djordjevic; Marko M. Folic; Slobodan M. Jankovic (Elsevier, 2017)
Hospital-acquired pneumonia (HAP) and ventilator-associated pneumonia (VAP) are the most common hospital infections with the highest prevalence in intensive care units (ICU). The aim of this study was to investigate prevalence of bacterial pathogens isolated from ICU patients with HAP/VAP and reveal their susceptibility rates in order to establish a basis for empirical antibiotic therapy. Prospective cohort study was conducted in central ICU of Clinical Centre Kragujevac, Serbia, from January 2009 to December 2015, enrolling 620 patients with documented HAP (38.2%) or VAP (61.8%).Gram-negative agents were isolated in 95.2%. Generally, the most common pathogens were Acinetobacter spp. and Pseudomonas aeruginosa, accounting for over 60% of isolates. The isolates of Acinetobacter spp. in HAP and VAP had low susceptibility to the 3rd generation cephalosporins, aminoglycosides, fluoroquinolones (0-10%). The rate of susceptibility to piperacillin-tazobactam was below 15%, whereas for carbapenems and 4th generation cephalosporins it was about 15-20%. Isolates of P. aeruginosa from HAP and VAP showed low susceptibility to ciprofloxacin and gentamicin (below 10%), followed by amikacin (25%), while the rate of susceptibility to carbapenems and 4th generation cephalosporin was 30-35%. Furthermore, 86% of isolates of P. aeruginosa non-susceptible to carbapenems were also non-susceptible to ciprofloxacin. The highest level of susceptibility from both groups was retained toward piperacilin-tazobactam. In ICU within our settings, with predominance and high resistance rates of Gram-negative pathogens, patients with HAP or VAP should be initially treated with combination of carbapenem or piperacillin-tazobactam with an anti-pseudomonal fluoroquinolone or aminoglycoside. Colistin should be used instead if Acinetobacter spp. is suspected. Vancomycin, teicoplanin or linezolide should be added only in patients with risk factors for MRSA infections. Keywords: Hospital-acquired pneumonia, Ventilator-associated pneumonia, Microbiology, Resistance rate